137 Enhancing road policing in low and middle income countries through the identification of good practice principles. (1st September 2016) - Watson, Barry; Bates, Lyndel; Pietro, Gayle Di; Inclan, Cristina
Abstract : Background: The implementation and enforcement of strong, evidence-based road safety laws and regulations has been shown to be highly effective in reducing road traffic deaths and injuries. In many low and middle income countries, however, the police do not have the necessary expertise or resources to implement good practice road policing in a sufficiently intense and sustained manner. Unfortunately, this can undermine the desired general deterrent effect of the enforcement and fail to communicate its purpose to the general community. The aim of this study was to identify the theoretical principles underpinning good practice road policing, in order to inform the development of relevant capacity-building initiatives in low and middle income countries. Methods: A review of the traffic law enforcement literature was undertaken to identify: i) the theoretical perspectives that have been used to guide the development and implementation of effective road policing programs; and ii) the specific principles arising from these perspectives that can be used to guide enforcement efforts in low and middle income countries. Results: The literature review identified a number of theoretical perspectives from criminology and traffic psychology that have been used to guide the development and delivery of effective road policing programs. Most prominent among these is deterrence theory, which has been extensively used to inform programs targeting illegal behaviours like drink driving and speeding. This perspective highlights the need for road policing operations to be as unpredictable, unavoidable and ubiquitous as possible to optimise general deterrence. More recently, applying the principles of procedural justice have been found to positively influence perceptions toward road policing among both the general community and operational police. Conclusions: In order to enhance road policing in low and middle income countries, consideration should be given to incorporating the theoretical perspectives and principles underpinning effective programs into relevant capacity-building programs.